Respuesta :

tonb
You do this by moving all terms without y to the right hand side, and then divide the whole lot to keep a clean y= on the left hand side.

Moving to the other side is done by subtracting (or adding) a term from both sides. Effectively this looks like you're moving the term and flipping the sign.

So 2y + 18 = 4x changes into 2y +18 -18 = 4x -18 so 2y = 4x - 18. If you forget about the middle step, it looks like the +18 jumped to the other side and changed sign. That's all.

Second step is to change the 2y into y. You do that by dividing everything by 2. So 2y=4x-18 becomes y=2x-9

1. y=2x-9
2. y=3/2x - 6
3. y=4x+18
4. y=2x-12

5. y=-4x+18
6. y=2/3x+4
7. y=-1/4x-18/4
8. y=1/4x-18/4

9. y=1/4x+18/4
10. y=-1/4x+18/4
11. y=-3/2x+6
12. y=3/2x+6

13. y=-3/2x-6
14. y=-2/3x-4
15. y=2/3x+2/3
16. y=18-4x 
ACCESS MORE